Impact of graft nephrectomy on outcomes of second kidney transplantation. (13th April 2014) - Fadli, Saâd Ed‐Dine; Pernin, Vincent; Nogue, Erika; Macioce, Valérie; Picot, Marie‐Christine; Ramounau‐Pigot, Annie; Garrigue, Valérie; Iborra, François; Mourad, Georges; Thuret, Rodolphe
<x xml:space="preserve">Abstract</x> Objectives To determine the impact of renal graft nephrectomy on second kidney transplantation survival. Methods We carried out a retrospective single‐center study by analyzing cases performed from January 2000 to December 2011. Retransplanted patients who underwent previous allograft nephrectomy more than 3 months post‐transplantation (group 1) were compared with those who did not (group 2) in terms of graft survival, incidences of acute rejection and delayed graft function. Multivariate Cox proportional hazard models were used to assess risk factors of graft loss after retransplantation. Results Overall, 146 patients were analyzed, including 52 (35.6%) in group 1 and 94 (64.4%) in group 2. Group 1 patients presented a significantly shorter first graft survival (0.8 vs 8.6 years, P < 0.001) and more anti‐class I antibodies (90.5% vs 74.2%, P = 0.03). A total of 10 patients (19%) in group 1 and 16 patients (17%) in group 2 had at least one acute rejection episode (P = 0.74). Delayed graft function was observed in 13 patients (25%) in group 1 and 17 patients (18%) in group 2 (P = 0.32). Graft survival at 1, 5 and 10 years was, respectively, 94%, 81% and 58% in group 1, and 99%, 93% and 66% in group 2 (P = 0.10). Graft survival was decreased by increased donor age and serum creatinine, and tended to be associated with post‐transplantation presence of anti‐class I and II antibodies. Graft nephrectomy was not associated with graft survival in multivariate analysis. Conclusions Graft nephrectomy, probably a marker of high immunological risk patients, is not a risk factor of increased retransplant failure.